Choline chloride. ZnCl2: Green, effective and reusable ionic liquid for synthesis of 7-amino-2, 4-dioxo-5-phenyl-2, 3, 4, 5-tetrahydro-1H-pyrano [2, 3-d] pyrimidine-6-carbonitrile derivative - Yadav D.K.; Quraishi M.A. (My University, 2025)
Pyrano [2, 3-d] pyrimidines could be synthesized using Lewis acid ionic liquid Choline chloride. ZnCl2 and triethanolamine as catalyst, as well as aromatic aldehydes, malononitrile and barbituric acid or 2-thiobarbituric acid as substrates. The ionic liquid showed good catalytic activity and reusable performance under mild conditions. The reaction proceeds smoothly under ultrasonic irradiation at 75 °C. This method provides several advantages such as being environmentally friendly, using a simple workup procedure, shorter reaction time and affording good yields.